Allocation of public resources to social projects in the town of Engativá (2014)
The allocation of resources to different sectors of the nation has been giving since quite time ago, in order to compensate, improve quality of life and satisfy some of the basic needs of citizens that live in the national territory, but many times we ask ourselves, how these resources are allocated?, what is their proportion to each region, municipality, district, city, mayoralty, town and projects.